(untitled) (Clinics, 2013)
OBJECTIVE: Lichen planus is a chronic inflammatory autoimmune mucocutaneous disease. Recent research has emphasized the strong association between inflammation and both P-wave dispersion and dyslipidemia. The difference between the maximum and minimum P-wave durations on an electrocardiogram is defined as P-wave dispersion. The prolongation of P-wave dispersion has been demonstrated to be an independent risk factor for developing atrial fibrillation. The aim of this study was to investigate P-wave dispersion in patients with lichen planus. METHODS: Fifty-eight patients with lichen planus and 37 age- and gender-matched healthy controls were included in this study. We obtained electrocardiographic recordings from all participants and used them to calculate the P-wave variables. We also assessed the levels of highly sensitive C-reactive protein, which is an inflammatory marker, and the lipid levels for each group. The results were reported as the means ± standard deviations and percentages. RESULTS: The P-wave dispersion was significantly higher in lichen planus patients than in the control group. Additionally, highly sensitive C-reactive protein, LDL cholesterol, and triglyceride levels were significantly higher in lichen planus patients compared to the controls. There was a significant positive correlation between highly sensitive C-reactive protein and P-wave dispersion (r = 0.549, p